Integration of Employment Law Regulations in the Omnibus Law: Impact on Workers' Rights and Obligations - Vais Vais; Nanda Agustin; Dini Eka Wardhani; Zahidatun Muti’ah Almina; Badrut Tamam (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
Related to Omnibuslaw currently has been established to be part of the Law, but there are some issues that cause overlap and inconsistency with workers. As well as the existence of the work creation law gives more freedom to entrepreneurs than to workers or workers, one of them is like giving hours of work and giving wages that are only unilaterally discontinued without a joint agreement. This is the problem that is considered serious because so many workers complain about the problem. Therefore, with the existence of the application of omnibuslaw to the law of creation of work to correct the imbalance that has occurred to entrepreneurs and workers. As with the establishment of government regulations replacing the Law No. 2 of 2022 on job creation, these new regulations were enforced with the aim of further maximizing and improving the welfare of workers or entrepreneurs based on Pancasila. Even with the implementation of omnibuslaw to improve the existing employment system in Indonesia.